Increasing Primary Care Engagement Among Homeless-Experienced Veterans Following an Emergency Department Visit: Qualitative Insights From Los Angeles County - Melissa Chinchilla; Kian Preston-Suni; Edwin Jacobo; Sonya Gabrielian (Journal of Primary Care & Community Health)
Background: Homeless-experienced persons that present in the Emergency Department (ED) often fail to receive follow-up primary care. To inform implementation of a post-ED patient navigation model, we engaged homeless-experienced Veterans to identify barriers to primary care and the acceptability of a peer-led intervention within the ED. Methods: Between August and November 2023, 3 focus groups (n = 14) and 2 interviews were held (total n = 16) with homeless-experienced Veterans who sought care in the Department of Veterans Affairs’ (VA) Greater Los Angeles (GLA) ED. We inquired about barriers to primary care post-ED visit, ways to improve connection, and the acceptability of a peer-led intervention. Fieldnotes were taken and coded using rapid qualitative methods. Results: Participants noted challenges receiving adequate information about and support connecting with primary care; challenges included lengthy appointment wait times, lack of knowledge regarding clinic walk-ins, and challenges with social needs. Recommendations for facilitating connection comprised support with patient navigation, including obtaining timely appointments, addressing social needs, and identifying healthcare priorities. Participants noted numerous benefits to having peers in the ED to assist with healthcare and resource connection. Conclusions: Data will inform future work to adapt and pilot a peer-led patient navigation model for homeless-experienced Veterans in VA GLA’s ED.